Pengaruh pergeseran struktural birokrasi terhadap pemanfaatan program siaran media radio pendidikan di Indonesia - Wahyudi Wahyudi (LPMPP Universitas Negeri Yogyakarta, 2006)
The radio as a type of audio media represents a product of communicatioan technology coming into birth as media of entertainment, informatioan, and education. Study and development on such media form the sake of the three fungtion are based on audience characteristics, program materials, and technikal develompent related to the technology to make communicationa occur more effectively. As one purpose of the utilization of the radio media is education, the utilazation and development of such audio medi for education have actually been going on a long time in Indonesia. But, though research results and empirical evidence related to the utilization of the radio media i Indonesia have once expreienced thir times of glory. they have now been decreasing.Trends or inclination factors in the current fast growing audio-visual media are not the only causes of the decreasing utilization of the readio media in education.